Lack of evidence for the effectiveness or safety of over-the-counter cannabidiol products - Edward Chesney; Philip McGuire; Tom P. Freeman; John Strang; Amir Englund (SAGE Publishing, 2020)
Over the past 5 years, public interest in the potential health benefits of cannabidiol (CBD) has increased exponentially, and a wide range of over-the-counter (OTC) preparations of CBD are now available. A substantial proportion of the population appears to have used these products, yet the extent to which they are effective or safe is unclear. We reviewed the evidence for whether CBD has significant pharmacological and symptomatic effects at the doses typically found in OTC preparations. We found that most of the evidence for beneficial effects is derived from studies of pure, pharmaceutical grade CBD at relatively high doses. Relatively few studies have examined the effect of OTC CBD preparations, or of CBD at low doses. Thus, at present, there is little evidence that OTC CBD products have health benefits, and their safety has not been investigated. Controlled trials of OTC and low-dose CBD preparations are needed to resolve these issues.